Desenvolvimento pós-embrionário de Ceraeochrysa cincta (Schneider, 1851) (Neuroptera: Chrysopidae) alimentada com ovos de Diatraea saccharallis (Fabricius, 1794) (Lepidoptera: Crambidae) - Amorim Pessoa, Luis Gustavo; de Freitas, Sergio [UNESP]; Loureiro, Elisangela de Souza (Universidade Estadual de Londrina (UEL), 2010)
The lacewings (Ceraeochrysa cincta) are important predators found associated to many pests in several agroecosystems. Eggs of Sitotroga cerealella and Anagasta kuehniella are used traditionally for massal rearing of these predators. Other foods can be used in substitution to the traditional ones, but little is known about the biology of lacewings and other alternative foods. So, this work was carried out to evaluate the effect of different diets on the post-embryonic development of C. cincta in laboratory. After been individualized in glass tubes, each larva was fed with S. cereallella and Diatraea saccharallis. It was evaluated the larvae duration, weight and viability in each instar, the duration, weight and viability of the pupa and pre-pupa stages and the duration of the post-embryonic period. It was adopted a completely randomized design with ten replications per treatment, each consisting of five eggs or larvae of C. cincta. Larvae were weighed 48 hours after hatching and 48 hours after each molt, and pre-pupae and pupae, 48 hours after starting these stages. There was no effect of the kind of food provided on the parameters evaluated. Therefore, D. saccharallis eggs can be used to feed C. cincta.
Post-embryonic development of Ceraeochrysa cincta (Schneider, 1851) (Neuroptera: Chrysopidae) fed with eggs of Diatraea saccharallis (Fabricius, 1794) (Lepidoptera: Crambidae)
Keywords: Lacewing; larval feeding; biological control